Associations of childhood, maternal and household dietary patterns with childhood stunting in Ethiopia: proposing an alternative and plausible dietary analysis method to dietary diversity scores - Melaku, Yohannes Adama (Nutr J, 2018)
BACKGROUND: Identifying dietary patterns that consider the overall eating habits, rather than focusing on individual foods or simple counts of consumed foods, better helps to understand the combined effects of dietary components. Therefore, this study aimed to use dietary patterns, as an alternative method to dietary diversity scores (DDSs), and investigate their associations with childhood stunting in Ethiopia. METHODS: Mothers and their children aged under 5 years (n = 3788) were recruited using a two-stage random cluster sampling technique in two regions of Ethiopia. Socio-demographic, dietary and anthropometric data were collected. Dietary intake was assessed using standardized dietary diversity tools. Household, maternal and child DDSs were calculated and dietary patterns were identified by tetrachoric (factor) analysis. Multilevel linear and Poisson regression analyses were applied to assess the association of DDSs and dietary patterns with height-for-age z score (HAZ) and stunting, respectively. RESULTS: The overall prevalence of stunting among children under-five was 38.5% (n = 1459). We identified three dietary patterns each, for households (“fish, meat and miscellaneous”, “egg, meat, poultry and legume” and “dairy, vegetable and fruit”), mothers (“plant-based”, “egg, meat, poultry and legume” and “dairy, vegetable and fruit” and children (“grain based”, “egg, meat, poultry and legume” and “dairy, vegetable and fruit”). Children in the third tertile of the household “dairy, vegetable and fruit” pattern had a 0.16 (β = 0.16; 95% CI: 0.02, 0.30) increase in HAZ compared to those in the first tertile. A 0.22 (β = 0.22; 95% CI: 0.06, 0.39) and 0.19 (β = 0.19; 0.04, 0.33) increase in HAZ was found for those in the third tertiles of “dairy, vegetable and fruit” patterns of children 24–59 months and 6–59 months, respectively. Those children in the second (β = −0.17; 95% CI: -0.31, −0.04) and third (β = −0.16; 95% CI: -0.30, −0.02) tertiles of maternal “egg, meat, poultry and legume” pattern had a significantly lower HAZ compared to those in the first tertile. No significant associations between the household and child “egg, meat, poultry and legume” dietary patterns with HAZ and stunting were found. Statistically non-significant associations were found between household, maternal and child DDSs, and HAZ and stunting. CONCLUSION: A higher adherence to a “dairy, vegetable and fruit” dietary pattern is associated with increased HAZ and reduced risk of stunting. Dietary pattern analysis methods, using routinely collected dietary data, can be an alternative approach to DDSs in low resource settings, to measure dietary quality and in determining associations of overall dietary intake with stunting. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12937-018-0316-3) contains supplementary material, which is available to authorized users.